1974
DOI: 10.1259/0007-1285-47-553-37
|View full text |Cite
|
Sign up to set email alerts
|

Depression of lymphocyte replicating ability in radiotherapy patients

Abstract: The effects of radiation upon circulating lymphocytes have been measured by two independent means, one monitoring the level of cytogenetic damage appearing in these cells, the other monitoring changes in their proliferative response to stimulation in culture by phytohaemagglutin (PHA). Response to PHA can be expressed quantitatively as lymphocyte replicating ability (LRA), i.e. the degree of 3 H-thymidine uptake measured under standardized conditions. Varying degrees of depression of LRA have been noted within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…Lymphocyte counts also decreased significantly following radiotherapy in lung cancer patients and are in general agreement with the findings of other investi gators in lung cancer [2,3,5,9,10] and other malig nancies (11,13].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Lymphocyte counts also decreased significantly following radiotherapy in lung cancer patients and are in general agreement with the findings of other investi gators in lung cancer [2,3,5,9,10] and other malig nancies (11,13].…”
Section: Discussionsupporting
confidence: 89%
“…There have been conflicting reports regarding cellmediated immunity in lung cancer patients. Some in vestigators have reported varying degrees of depression of lymphocyte transformation in lung cancer patients following radiotherapy [1][2][3][4][5] while others have not observed such a reduced response [6][7][8], To date there is very little quantitative data on lymphocyte survival in lung cancer patients undergoing radiotherapy. This report describes in vivo and in vitro survival of lympho cytes in lung cancer patients before, during and follow ing radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, others described RT as an immunosuppressant (29). Lymphocytes are exquisitely sensitive to the effects of RT (30)(31)(32), and irradiating the tumor target could potentially eliminate antitumor immune activity. This, along with the general ineffectiveness of RT on local control and of early immunotherapies on systemic disease, dampened enthusiasm for pursuing the combination.…”
Section: Immunomodulatory Properties Of Rtmentioning
confidence: 99%
“…Radiotherapy has been widely believed to suppress the host's immune system [1][2][3][4][5][6][7], Recent studies, how ever, have demonstrated that an enhanced local im mune reaction, i.e., infiltration of numerous T lym phocytes in and around the tumor tissue, can be seen transiently during radiotherapy [8 11]. To learn whether this phenomenon really represents an ac tivated immune reaction specific against tumor cells, it is necessary to investigate the composition and func tion of the infiltrated lymphocytes.…”
Section: Introductionmentioning
confidence: 99%